eZ-BAYAN: an Interactive tools to learn Science of al-Bayan (Arabic Rhetoric) - Awang Ali, Mohammad Amnan; Engku Mohamaed Nor, Engku Amir Hamzah; Abdul Rahim, Abdul Hadi (Research, Industrial Linkages, Community, and Alumni Division Universiti Teknologi MARA, Cawangan Negeri Sembilan, 72000 Kuala Pilah, Negeri Semblan, Malaysia, 2021)
The purpose of this study is to help Arabic language learners at the Department of Arabic Language and Literature of International Islamic University Malaysia (IIUM) in learning ‘Science of al-Bayan’ by designing prototype courseware for them. This study was conducted using systematic descriptive and analytical methodologies. The descriptive approach required the researcher to gather information about the ‘Science of al-Bayan’ and learning theories through an educational blog. In addition, there were several stages of scientific procedures in the analytical approach. First and foremost, learners’ needs analysis was conducted before the phase of design. Secondly, experts’ review analysis was conducted during the design phase. The next stage was the analyses of the results of pre-and post-tests done by learners. Lastly, the analysis of formative evaluation by the learners after the completion of the development phase was also conducted. Special prototype courseware in learning ‘Science of al-Bayan’ was designed using an educational blog based on the ADDIE instructional design model in the design and development process based on students’ needs, opinions, and suggestions. The participants were 60 students (27 students were selected during the needs analysis phase and 33 students were chosen during the pre- and post-tests and the evaluation phase). Two experts were selected from Computer Assisted Instruction (CAI) and Arabic Rhetoric during the needs analysis phase. This study showed that most students were optimistic about learning ‘Science of al-Bayan’ through the educational blog, which increased their learning desires and motivation and improved their understanding and performance in learning this subject.